If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x * 7 = 5x + -6x Reorder the terms for easier multiplication: 14 * 7x = 5x + -6x Multiply 14 * 7 98x = 5x + -6x Combine like terms: 5x + -6x = -1x 98x = -1x Solving 98x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 98x + x = -1x + x Combine like terms: 98x + x = 99x 99x = -1x + x Combine like terms: -1x + x = 0 99x = 0 Divide each side by '99'. x = 0 Simplifying x = 0
| -8x+4(x+6)=20 | | 5(4n-8)=-28+8n | | -3(r+4)=-41 | | k+4-7=3 | | 2.1x+45.2+3.2-824x= | | -16w+7.38=-16.7w+2.97 | | 7y+49=9(y+7) | | 7r-6r=5 | | 20=10v-5v | | 6=-6u+4(u+4) | | 6m-2=32 | | 0.3x=0.09 | | 6(x+3)=3(8+4x)-6 | | 20-14s=-20-19s | | 2-15-5=12 | | 4(x-3)+5=53 | | 4(2w-3)=2(3w+5) | | t^3+6t^2=25t+150 | | 3(X-2)=Xm+7 | | 5x+6=2x-2 | | 14=-5y+3(y-2) | | 18y=-20+19y | | -17-4k=3k+13-5k | | 0=-7r-3r | | 3(2x+5)=-37+22 | | 29=8+3x | | 25(x^2)-20x+4=0 | | 3g+9=4g | | 10-7k=-(8k-7) | | 8-9z=-5z | | 5-3(X-4)=11 | | -8=6(v-4)-8v |